Height of entire house = height of first floor + height of second floor + height of attic
Rearrange to make "Height of attic" the subject
To do this, place "height of first floor" and "height of second floor on the other side of the equation"
So:
Height of attic = Height of entire house - height of first floor - height of second floor
Height of attic = 241/3 - 85/6 - 81/2
Next problem, they are all in fractions.
So make a common/same denominator (bottom number)
Let's make the common denominator 6.
241/3 x 2/2 = 482/6
*It still has the same value
85/6 already has a denominator of 6 so no need to do anything to it.
81/2 x 3/3 = 243/6
Height of attic = 482/6 -85/6 -243/6
Simplify it to one fraction since they all have the same denominator now:
Height of attic = (482 - 85 - 243) / 6
Height of attic = 154/6